Penyelesaian Hukum Klausula Baku dalam Perjanjian Electronic Commerce Ditinjau dari Aspek Hukum Perlindungan Konsumen - Andi Mamora Siregar (LPPM Universitas Ekasakti Padang, 2023)
The dominant influence of technology, especially the internet, and smartphones, on almost all aspects of human life. Internet technology, which was originally only used for office activities, has now penetrated various lines of life through mobile devices. Smartphones have become multifunctional tools, from making phone calls to banking transactions, and various other applications that facilitate human life. One application that attracts attention is online shopping applications. Although it provides convenience, the application also raises several issues, especially regarding the rights and obligations between sellers and buyers. In Indonesia, online shopping transactions through Electronic Commerce often lead to consumer protection issues that feel harmed by service providers. These cases often involve the use of standard clauses by online shopping service providers to avoid claims from consumers.